(untitled) (Journal of Informatics and Mathematical Sciences, 2021)
In this paper, the author contributed the concepts of fuzzy soft positive implicative hyper BCK-ideal of types \((,,)\), \((,,)\) and \((,,)\) are introduced some related properties are considered. Relations between double-framed soft hyper BCK-ideal and double-framed soft strong hyper BCK-ideal are discussed. Additionally, the author demonstrate that the level set of fuzzy soft positive implicative hyper BCK-ideal of types \((,,)\), \((,,)\) and \((,,)\) are positive implicative hyper BCK ideal of types \((,,)\), \((,,)\) and \((,,)\), respectively. The conditions for a fuzzy soft set to be a fuzzy soft positive implicative hyper BCK-ideal of types \((,,)\), \((,,)\) and \((,,)\), are initiated respectively, and the circumstances for a fuzzy soft set to be a fuzzy soft weak hyper BCK-ideal are also considered.